PENCATATAN NAMA PADA DOKUMEN KEPENDUDUKAN MENURUT PERATURAN MENTERI DALAM NEGERI REPUBLIK INDONESIA NOMOR 73 TAHUN 2022 - Farida Nur Aini; Oti Kusumaningsih (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
A name is a term used to address someone and as personal identification on citizen documents. The recording of names on citizen documents needs to be regulated as a guideline for residents and officials authorized to carry out records to facilitate public services. The government issued Permendagri number 73 of 2022 as guidelines for recording names, guidelines for writing names on citizen documents, and increasing legal certainty on citizen documents. Apart from that, it is also to facilitate public administration services, legal protection, fulfillment of constitutional rights and realize orderly public administration.